The Use of Abdominal Paracentesis in the Diagnosis of Ectopic Pregnancy in a Resource - Limited Setting - Awoleke JO; Akintayo AA (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2017)
Ectopic pregnancy remains an important cause of morbidity and mortality in the fi rst trimester of pregnancy, and has become a major public health challenge among women in the reproductive age group in this environment. A review of 139 consecutive cases of tubal ectopic gestations managed over a fi ve year period at the Ekiti State University Teaching Hospital, Ado - Ekiti, Nigeria was conducted. Ectopic pregnancies accounted for 1.8% of all deliveries. Most of the women were married (68.3%), between 26 - 30 years (28.8%) and of low parity [0 and 1] (61.9%), and all had abdominal pain. Induced abortion (72.7%) was the commonest factor and the levonorgestrel-containing pill was the commonest contraceptive (19/43) associated with ectopic pregnancy. 16.5% were severely anaemic at presentation, 1 in 6 women had prior uterine evacuation as a result of wrong diagnosis, 26.7% had massive haemoperitoneum (≥2000 millilitres) and salpingectomy (84.1%) was the commonest operative procedure. Paracentesis was positive in 84.6% of cases and negative in the only unruptured case. The correct diagnosis was missed in a third of the patients at presentation. The case fatality rate was 0.7%.  While improved diagnostic methods will reduce late presentations and tubal rupture, thereby improving the chances of tubal salvage and future reproductive outcome, a diagnostic algorithm that will include abdominal paracentesis may help to increase the pickup rate of ectopic pregnancy and be an impetus for immediate intervention in resource-poor settings.